Morphological identification of haematopoietic cells in pronephros of common carp (Cyprinus carpio Linnaeus, 1758) - Suljević, Damir; Islamagić, Erna; Alijagić, Andi; Fočak, Muhamed; Mitrašinović-Brulić, Maja (Acta Biologica Szegediensis, 2016)
Haemopoietic tissue of the common carp pronephros (Cyprinus carpio Linnaeus, 1758) was studied in regard of morphometric analysis of the erythropoietic, leukopoietic and thrombopoietic cell populations. The aim of this study was to perform evaluation of immature precursor cells in head kidney of common carp (sampled from Bardaca lake) because there is no well known data regarding this issue. Microscopic identification of haematopoietic cells included measurement of cell and nuclear size, nuclear-cytoplasmic ratio, determination of the cell and nuclear shape, cytosol coloration and presence of specific granules in the cytosol. The frequency of immature cells and their cell area was also analyzed. Erythroblasts were the most abundant among all observed haemopoietic cell lineages and were the most variable in the size. The largest area was characteristic of monocyte precursors and no significant differences were observed regarding the cell area between prothrombocytes and lymphoblasts, which makes difficult in cell characterization. High number of emerged cells in short time also makes difficult to identify particular stages of maturation in some bloodlines. Rapid maturation of granuloid cells observed within the haemopoietic tissue indicates their functional significance in adaptation to the changeable microenvironment.